DECISION SUPPORT FOR THE SELECTION OF TABLE EGG SUPPLIERS - Nedeljković, Miroslav; Vujić, Emilija; Krstić, Svetozar (Economics of Agriculture, 2025)
In the paper, for the purpose of selecting a supplier of table eggs in an agribusiness company, a multi-criteria decision-making method was applied. Through expert opinion, ten given criteria were evaluated using the fuzzy variant of the Simple Weight Calculation (SiWeC) method, and the selection itself was made using the COmpromise Ranking from Alternative Solutions (CORASO) method. The results show that the best rated criterion is „product quality”, while the choice for the best supplier went to the first supplier. The research confirms a successful and systematic approach in the application of the used method, as well as a literary contribution in the complex situation of supplier selection. In future research, it is necessary to expand the selection model in the analyzed area, as well as to include a larger number of decision makers and evaluation criteria. Also, it is necessary to continue improving the existing research method.